ChemInform Abstract: One Hundred Years of Helicene Chemistry. Part 2. Stereoselective Syntheses and Chiral Separations of Carbohelicenes. Issue 23 (16th May 2013) - Gingras, Marc; Felix, Guy; Peresutti, Romain
Abstract Review: 191 refs.